Epistemology of Decision Rational Choice, Neuroscience and Biological Approaches - Graziano, Mario. (SpringerBriefs in Philosophy, 2013)
This bookcarries out an epistemological analysis of the decision, including a critical analysis through the continuous reference to an interdisciplinary approach including a synthesis of philosophical approaches, biology and neuroscience. Besides this it represents the analysis of causality here seen not from the formal point of view,but fromthe"embodied" point of view.